Revealing the pace of river landscape evolution during the Quaternary: recent developments in numerical dating methods. (15th June 2017) - Rixhon, Gilles; Briant, Rebecca M.; Cordier, Stéphane; Duval, Mathieu; Jones, Anna; Scholz, Denis
Abstract: During the last twenty years, several technical developments have considerably intensified the use of numerical dating methods for the Quaternary. The study of fluvial archives has greatly benefited from these enhancements, opening new dating horizons for a range of archives at distinct time scales and thereby providing new insights into previously unanswered questions. In this contribution, we separately present the state of the art of five numerical dating methods that are frequently used in the fluvial context: radiocarbon, Luminescence, Electron Spin Resonance (ESR), 230 Th/U and terrestrial cosmogenic nuclides (TCN) dating. We focus on the major recent developments for each technique that are most relevant for new dating applications in diverse fluvial environments and on explaining these for non-specialists. Therefore, essential information and precautions about sampling strategies in the field and/or laboratory procedures are provided. For each method, new and important implications for chronological reconstructions of Quaternary fluvial landscapes are discussed and, where necessary, exemplified by key case studies. A clear statement of the current technical limitations of these methods is included and forthcoming developments, which might possibly open new horizons for dating fluvial archives in the near future, are summarised. Highlights: We present the state of the art of five numerical dating methods, frequently used in the fluvial context. The methods are: 14 C, Luminescence, Electron Spin Resonance, U-series and terrestrial cosmogenic nuclides dating. We focus on the major recent developments, relevant for new dating applications in diverse fluvial environments. Current technical limitations and forthcoming developments are also tackled.